Natural solutions for diabetes: the therapeutic potential of plants and mushrooms - Sknepnek, Aleksandra; Miletić, Dunja; Stupar, Alena; Salević-Jelić, Ana; Nedović, Viktor; Cvetanović Kljakić, Aleksandra (Frontiers in Nutrition, 2025)
Medicinal plants and mushrooms have been used for the prevention and treatment of various diseases since ancient times. For thousands of years, they have attracted significant interest due to their broad spectrum of biological activities and drug-like properties. Their continued use in traditional medicine has evolved alongside, and increasingly been supported by modern scientific research. Diabetes mellitus poses a serious global health, social and economic challenge and is among the most rapidly growing health issues of the 21st century. Type 2 diabetes mellitus (T2DM), which accounts for 90–95% of diabetes cases, is largely attributed to sedentary lifestyles, unhealthy diets and obesity. Herbal medicine has already played a key role in the development of antidiabetic drugs, as exemplified by the plant-derived origins of metformin. The development of new therapeutics or therapeutic adjuvants from natural sources offers several advantages over synthetic drugs, including improved safety profiles for long-term use, efficacy, affordability and reliance on renewable raw materials. This review highlights the potential of bioactive compounds from medicinal plants and mushrooms, discussing their mechanism of action, extraction techniques and their significance for the prevention, management and treatment of T2DM.